THE SPATIAL PRACTICES OF HOSPITALITY IN INDONESIAN ISLAMIC UNIVERSITY STUDENT HOUSING - Muhammad Ismail Hasan; Asrul Mahjuddin Ressang Aminuddin; Hazrina Haja Bava Mohidin (Journal of Islamic Architecture, 2023)
This study elucidates the hospitality practices by male and female students in selected Islamic university student housing (ISH) to propose the design framework emphasizing the spatiality values as social sustainability. Hospitality is seen as a significant aspect of Indonesian culture, which means acceptance and paying respect to other people in our own space. This culture is perceived as an entity in locality values that needs to be accommodated as the lesson learned for students during their stay in Islamic student housing. The study employs senior students to participate in Focus Group Discussions (FGD) to share their experiences regarding living in the multiuser bedroom. Qualitatively, the data are being analyzed using Atlas.ti to illustrate the intercorrelated codes towards the emergence of hospitality mechanisms among students. During their stay in Islamic student housing, joint activities conducted by students emerge with local values in hospitality action that enhance their social connectedness among their roommates and housemates. The analysis found that designated spaces must accommodate their activities toward social sustainability in design. This study is fruitful for the future design of Islamic student housing that considers local values in hospitality for social sustainability.